Antineutrophil cytoplasmic antibody-associated vasculitis with alveolar hemorrhage and ruptured renal aneurysm: A case report and literature review. Issue 1 (7th January 2022) - Tong, Jin; Zhou, Zhi-Yu; Liu, Xi; Wang, Dao-Xin; Deng, Wang
Abstract: Rationale: Antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV) is characterized by necrotizing damage to small-vessel vasculitis and mainly occurs in the kidney or lung. We report a rare case of AAV manifesting as alveolar hemorrhage and a renal aneurysm. Patient concerns: A 50-year-old Chinese man presented with repeated coughing, expectoration, fever, hypoxemia, and respiratory failure. The patient suffered from rupture of the renal aneurysm during immunosuppressive therapy. Diagnosis: Considering the clinical picture (fever, progressive hypoxemia, renal insufficiency, hemorrhagic bronchoalveolar lavage fluid, and left retroperitoneal hematoma) along with cANCA-PR3 positivity, and lung biopsy findings, the patient was finally diagnosed with granulomatosis with polyangiitis complicated by alveolar hemorrhage and renal aneurysm. Interventions: The patient was initially treated with immunosuppressive therapy combined with plasma exchange and subsequently with renal arterial embolization due to rupture of the renal aneurysm. Outcomes: The general condition and inflammatory reaction improved with immunosuppressive therapy combined with plasma exchange. Unfortunately, the patient did not respond to treatment and eventually died of respiratory failure and acute kidney injury after the rupture of the renal aneurysm. Lessons: We encountered unprecedented difficulties and challenges with renal aneurysm rupture. The possibility of aneurysmal rupture should be carefully considered and frequently checked for immunosuppressive therapy for AAV.